Impact of Micro Business Enterprise Act on the Growth and Development of Micro-Entrepreneurs in the Province of Bataan, Philippines - Allyses Alera; Jimelyn H. Evangelista; Jackielyn C. Cipriano (Politeknik Pariwisata Bali, 2022)
This research covers micro-entrepreneurs with BMBE certification in the Province of Bataan, Philipine. Impact assessment of BMBE will be measured in terms of profit maximization, increase capitalization, effective marketing tools, improve technology utilization and increased job generation. Questionnaires are provided to BMBE certificate holders to determine the level of impact on the growth and development of micro-entrepreneurs. The quantitative approach is employed for this study to understand the general characteristics of the population using survey questionnaire. The appropriate sample for this study was determined using statistical G-Power Analysis Software. The statistical tests used were weighted mean, frequency and percentage for the descriptive statistics while for inferential statistics, paired samples t-test, and regression analysis were utilized. Weighted mean was utilized to describe the BMBE incentives paired samples t-test was used to compare the growth and development of the previous and current years. The frequency result for micro-entrepreneurs shows that respondents “Sometimes” avail BMBE incentives. Results showed that BMBE incentives availed by owners proved to have no significant impact to profit maximization. Meanwhile, BMBE incentives has positive significant on increase on capitalization. Lastly, the average job growth rate of the respondents is 237%.